Impaired cerebellar Purkinje cell potentiation generates unstable spatial map orientation and inaccurate navigation - Julie Marie Lefort (Nature Portfolio, 2019)
It is known that Purkinje cell PKC-dependent depression is involved in the stabilization of self-motion based hippocampal representation. Here the authors describe decreased stability of hippocampal place cells based on allocentric cues in mice lacking Purkinje cell PP2B-dependent potentiation.